2016
DOI: 10.1097/sla.0000000000001768
|View full text |Cite
|
Sign up to set email alerts
|

Is Centralization Needed for Esophageal and Gastric Cancer Patients With Low Operative Risk?

Abstract: To improve POM, esophageal and gastric cancer surgery should be centralized, irrespective of the patient's comorbidity or tumor location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 19 publications
1
47
0
1
Order By: Relevance
“…This expected difference may be counteracted by the higher percentage of patients with a co‐morbidity score of 3 or more and the larger proportion who had a total gastrectomy in high‐volume hospitals compared with lower‐volume hospitals. Postoperative mortality was low for each hospital volume category compared with rates in a retrospective French study that reported the impact of centre volume on postoperative mortality after gastric cancer surgery. In that study, the postoperative mortality rate ranged from 4·3 to 10·2 per cent, and was 7·9 per cent in very high‐volume hospitals (at least 60 resections/year); it should be noted that the majority of patients had a cardia tumour.…”
Section: Discussionmentioning
confidence: 92%
“…This expected difference may be counteracted by the higher percentage of patients with a co‐morbidity score of 3 or more and the larger proportion who had a total gastrectomy in high‐volume hospitals compared with lower‐volume hospitals. Postoperative mortality was low for each hospital volume category compared with rates in a retrospective French study that reported the impact of centre volume on postoperative mortality after gastric cancer surgery. In that study, the postoperative mortality rate ranged from 4·3 to 10·2 per cent, and was 7·9 per cent in very high‐volume hospitals (at least 60 resections/year); it should be noted that the majority of patients had a cardia tumour.…”
Section: Discussionmentioning
confidence: 92%
“…Although centralization of oesophageal and pancreatic cancer surgery improves overall survival, the benefits of centralizing gastric cancer surgery seem ambiguous according to previous studies 11,17,24 . Some studies reported reduced postoperative mortality and better overall survival for patients who underwent gastrectomy after centralization, but others found no improvement in overall survival, probably related to the small number of patients included 10,11,16 .…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the definition of 'high volume' varied significantly between the different studies [22,26]. This effect was reproduced in several more recent studies in Europe and the USA [14][15][16][17][27][28][29][30][31].…”
Section: Association Between Hospital Volume and Surgical Outcome In mentioning
confidence: 53%
“…Several studies analyzing the correlation between postoperative mortality and hospital volume show a significant decrease in mortality in centers with 20 or more procedures a year [16,36]. A recent study from France even demonstrates a further reduction in postoperative mortality in centers with more than 40 or more than 60 procedures per year even for low-risk patients [31], and results from a large European multicenter trial demonstrate a significant reduction of postoperative mortality for a procedural volume of more than 80 operations per year [28]. A study from the Netherlands in more than 10,000 patients suggests that postoperative mortality reaches a plateau after 40-60 esophagectomies per year [30], indicating a reasonable cut-off far from the minimum caseload required in Germany.…”
Section: Esophageal Surgery In Germany: Minimum Caseload Requirementsmentioning
confidence: 97%